A human-centered perspective on research challenges for hybrid human artificial intelligence in lifestyle and behavior change support - Hao, Chenxu; Uusitalo, Susanne; Figueroa, Caroline; Smit, Quirine T. S.; Strange, Michael; Chang, Wen-Tseng; Ribeiro, M. I.; Kouomogne Nana, Vanita; Tielman, Myrthe L.; de Boer, Maaike H. T. (Frontiers in Digital Health, 2025)
As intelligent systems become more integrated into people’s daily life, systems designed to facilitate lifestyle and behavior change for health and well-being have also become more common. Previous work has identified challenges in the development and deployment of such AI-based support for diabetes lifestyle management and shown that it is necessary to shift the design process of AI-based support systems towards a human-centered approach that can be addressed by hybrid intelligence (HI). However, this shift also means adopting a user-centric design process, which brings its own challenges in terms of stakeholder involvement, evaluation processes and ethical concerns. In this perspective paper, we aim to more comprehensively identify challenges and future research directions in the development of HI systems for behavior change from four different viewpoints: (1) challenges on an individual level, such as understanding the individual end-user’s context (2) challenges on an evaluation level, such as evaluation pipelines and identifying success criteria and (3) challenges in addressing ethical implications. We show that developing HI systems for behavior change is an interdisciplinary process that requires further collaboration and consideration from various fields.